2016
DOI: 10.1007/s11356-016-7074-6
|View full text |Cite
|
Sign up to set email alerts
|

Herbicide micropollutants in surface, ground and drinking waters within and near the area of Zagreb, Croatia

Abstract: The frequency and mass concentrations of 13 herbicide micropollutants (triazines, phenylureas, chloroacetanilides and trifluralin) were investigated during 2014 in surface, ground and drinking waters in the area of the city of Zagreb and its suburbs. Herbicide compounds were accumulated from water by solid-phase extraction using either octadecylsilica or styrene-divinylbenzene sorbent cartridges and analysed either by high-performance liquid chromatography with UV-diode array detector or gas chromatography wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(31 citation statements)
references
References 52 publications
(68 reference statements)
1
26
0
1
Order By: Relevance
“…TBA was among the most detected pesticides, posing a relevant risk for the environment, with 436 positive findings, 95 of which exceeded the 'predicted no effect concentration' (Tsaboula et al 2016). In Switzerland the highest levels of the herbicide were found in April during a 4-month monitoring study of the Sion-Riddes canal, which corresponded to the period of TBA application on crops (Schopfer et al 2014), while maximum TBA and DET contamination levels were observed from April to August in surface waters of Croatia, shortly after field application of TBA (Fingler et al 2017).…”
Section: Surface Watersmentioning
confidence: 99%
See 3 more Smart Citations
“…TBA was among the most detected pesticides, posing a relevant risk for the environment, with 436 positive findings, 95 of which exceeded the 'predicted no effect concentration' (Tsaboula et al 2016). In Switzerland the highest levels of the herbicide were found in April during a 4-month monitoring study of the Sion-Riddes canal, which corresponded to the period of TBA application on crops (Schopfer et al 2014), while maximum TBA and DET contamination levels were observed from April to August in surface waters of Croatia, shortly after field application of TBA (Fingler et al 2017).…”
Section: Surface Watersmentioning
confidence: 99%
“…TBA and DET have frequently been detected in groundwaters around Zagreb in Croatia; during a monthly campaign conducted in 2014, TBA was detected in 26% of samples, up to 25 ng L -1 (Fingler et al 2017). The Vistrenque shallow alluvial aquifer (France) was tested between 2011 and 2013, where TBA was found in 59% of the 66 samples collected, up to 40 ng L -1 (Sassine et al 2017).…”
Section: Groundwatermentioning
confidence: 99%
See 2 more Smart Citations
“…If a herbicide is applied before crop emergence (as in this study), then only a very small portion will be absorbed by plant roots (13), while the bulk will remain in soil from where it can enter surrounding waters (10,(14)(15)(16). The mobility of a herbicide (leaching/runoff) or its retention in soil (adsorption) is highly affected by its characteristics (such as hydrophobicity), soil type (pH and humus/clay content), and soil moisture level and temperature (6,8,17).…”
mentioning
confidence: 99%